A Random-Matrix-Theory-Based Analysis of the Brazilian Stock Market During the 2008 Financial Crisis and Asian Crisis and Temporal Neighborhoods - Aires, Debora Barbosa [UNESP]; Crepaldi, Antonio Fernando [UNESP] (World Scientific Publ Co Pte Ltd, 2022)
Several approaches and concepts of physics, such as Random Matrix Theory, have been used to investigate the complexity of financial time series. This study aims to analyze the spectrum of stock correlation in the Brazilian stock market by applying Random Matrix Theory to the subprime and Asian financial crisis periods and their temporal neighborhoods. Results show evident synchronized market behavior during both crises. The results also show that the period preceding a crisis presents symptoms which may predict future crises. Thereby, the methodology presented here could be used by the market as a tool that helps to anticipate possible market fluctuations.
Keywords: Cross-correlation analysis; Random matrix theory; 2008 financial crisis; Asian financial crisis; Brazilian stock market